Isolation of Mouse Cerebral Microvasculature for Molecular and Single-Cell Analysis - Paraiso, Hallel C.; Wang, Xueqian; Kuo, Ping-Chang; Furnas, Destin; Scofield, Barbara A.; Chang, Fen-Lei; Yen, Jui-Hung; Yu, I-Chen (Frontiers in Cellular Neuroscience, 2020)
Brain microvasculature forms a specialized structure, the blood-brain barrier (BBB), to maintain homeostasis and integrity of the central nervous system. The BBB dysfunction is emerging as a critical contributor to multiple neurological disorders, including stroke, traumatic brain injury, autoimmune multiple sclerosis, and neurodegenerative diseases. The brain microvasculature exhibits highly cellular and regional heterogeneity to accommodate dynamic changes of microenvironment during homeostasis and diseases. Thus, investigating the underlying mechanisms that contribute to molecular or cellular changes of the BBB is a significant challenge. Here, we describe an optimized protocol to purify microvessels from the mouse cerebral cortex using mechanical homogenization and density-gradient centrifugation, while maintaining the structural integrity and functional activity of the BBB. We show that the isolated microvessel fragments consist of BBB cell populations, including endothelial cells, astrocyte end-feet, pericytes, as well as tight junction proteins that seal endothelial cells. Furthermore, we describe the procedures to generate single-cell suspensions from isolated microvessel fragments. We demonstrate that cells in the single-cell suspensions are highly viable and suitable for single-cell RNA-sequencing analysis. This protocol does not require transgenic mice and cell sorting equipment to isolate fluorescence-labeled endothelial cells. The optimized procedures can be applied to different disease models to generate viable cells for single-cell analysis to uncover transcriptional or epigenetic landscapes of BBB component cells.